2023
DOI: 10.1002/cctc.202201670
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Layer Support Structures on the Catalytic Activity of NiFe(oxy)hydroxide (LDH) for the OER in Alkaline Media

Abstract: Photoelectrochemical (PEC) cells promise to combine the benefits of photovoltaics and electrolysis in one device. They consist of a photoabsorber functionalized with an electrocatalyst to harvest faradaic currents under reduced overpotentials. To protect the absorber from the harsh reaction conditions, a protective buffer layer (e. g. TiO2) is added between absorber and catalyst. In this work, we investigate the influence of the catalyst support systems Ti/TiOx and Ti/TiOx/M (M=Au, Ni, Fe) on the overall activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…8b) and may also contribute to the increased OER activity. Recent work by Strasser et al 75 demonstrated that the presence of a metal support layer such as Au, Ni or even Fe between Ti/TiO 2 and NiFe(oxy)hydroxide (LDH) materials can also significantly improve the OER activity. This is not simply due to an increase in conductivity but that the morphology and the related electronic structure between the catalyst and the substrate material as well as between the metal interlayer and the substrate play an important role for the finally observed improved activity.…”
Section: Resultsmentioning
confidence: 99%
“…8b) and may also contribute to the increased OER activity. Recent work by Strasser et al 75 demonstrated that the presence of a metal support layer such as Au, Ni or even Fe between Ti/TiO 2 and NiFe(oxy)hydroxide (LDH) materials can also significantly improve the OER activity. This is not simply due to an increase in conductivity but that the morphology and the related electronic structure between the catalyst and the substrate material as well as between the metal interlayer and the substrate play an important role for the finally observed improved activity.…”
Section: Resultsmentioning
confidence: 99%
“…Typical NiO x H y films were electrodeposited on Ni foil (NF) substrates to avoid interference from substrate effects. 19,[30][31][32] Prior to deposition, substrates were cleaned in ethanol and 3 M HCl under sonication, rinsed with 18.2 MO cm deionized water, and dried. Films were cathodically deposited using a twoelectrode setup and a 20 mM nickel(II) nitrate aqueous solution (pH B 3).…”
Section: Electrocatalytic Film Preparation and Characterizationmentioning
confidence: 99%
“…As noted previously, results for the TM selenide data set (Figure b) indicate that the surface area, via the double-layer capacitance, and the type of substrate significantly influence the outcome as precatalyst, suggesting a link to the reconstruction of precatalysts and enhancement of catalytic activity. Previous works have linked substrate effects to OER activity enhancement in transition metal oxyhydroxide catalysts. More experimental and computational studies are necessary to explore the role of these extrinsic properties on the performance and transformation of TM X-ides. Furthermore, studies could explore how postreconstruction morphologies affect bubble removal, which is crucial for industrial water electrolysis, along with the reconstruction’s impact on mechanical stability, surface roughness, and corrosion over time. ,, Investigations at higher and fluctuating currents are also pertinent …”
Section: Perspectives and Research Directionsmentioning
confidence: 99%